Postimplantation syndrome after endovascular aortic repair: Impact of endograft material and a review of the literature - Bahadir Aytekin; Hakki Zafer Iscan (Turkish Journal of Vascular Surgery)
Aim: Postimplantation syndrome (PIS) is a systemic inflammatory response occurring acutely after endovascular aneurysm repair (EVAR), with reported incidence ranging from 14% to 60%. This study aimed to evaluate the association of different endograft materials with the manifestation and severity of PIS and the role of thrombus formation with type II endoleak incidence. Material and Methods: A retrospective analysis was performed on data from patients who underwent elective EVAR between January 2021 and January 2024. After applying inclusion and exclusion criteria, 171 patients were included. The patients had a mean age of 70.3±8.6 years and 93% were male. Patients were divided into PIS and Non-PIS groups, with a subgroup analysis within the PIS group comparing polyester and expanded polytetrafluoroethylene (e-PTFE) materials. Patient outcomes post-discharge and within the first-year post-surgery were evaluated. Results: No early mortality was observed. PIS was diagnosed in 39.2% of the patients. There was no significant difference on longer intensive care unit (ICU) or hospital stays among the PIS and Non-PIS groups. The incidence of PIS was significantly higher in the polyester subgroup (60%) compared to the ePTFE subgroup (25%). Univariate logistic regression identified polyester material as the factor associated with PIS (P=0.03). First-year computed tomographic angiography (CTA) follow-ups showed a statistically significant lower incidence of type II endoleak (p=0.01) and higher new thrombus formation (p=0.04) in the polyester group. Conclusion: Following EVAR, the patients experience systemic inflammatory responses influenced by the choice of endograft material. Polyester endografts are associated with a higher incidence of PIS and thrombogenicity but a lower incidence of type II endoleak in our study. [Turk J Vasc Surg 2024; 33(2.000): 97-102]